2010
DOI: 10.1016/j.tet.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric reduction of aliphatic ketones and acyl silanes using chiral anti-pentane-2,4-diol and a catalytic amount of 2,4-dinitrobenzenesulfonic acid

Abstract: Abstract-Aliphatic ketones were reduced to the corresponding secondary alcohols by using anti-1,3-diol and a catalytic amount of 2,4-dinitrobenzenesulfonic acid (DNBSA) in benzene at reflux. Addition of 1-octanethiol in that media improved the efficiency of the reduction. Asymmetric reduction of aliphatic ketones was performed by using chiral anti-pentane-2,4-diol, and highly asymmetric induction (up to >99% ee) was observed in the reduction of tert-alkyl ketones. Asymmetric reduction of acyl silanes using chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Two significant reports from the Matsuo group concern ketone reduction by 1,3-diols in the presence of catalytic 2,4-dinitrobenzenesulfonic acid. 225,226 This methodology arose from a serendipitous observation of ketone reduction as opposed to the expected ketal formation. The group have shown that enantioinduction up to 99% e.e.…”
Section: Scheme 42mentioning
confidence: 99%
“…Two significant reports from the Matsuo group concern ketone reduction by 1,3-diols in the presence of catalytic 2,4-dinitrobenzenesulfonic acid. 225,226 This methodology arose from a serendipitous observation of ketone reduction as opposed to the expected ketal formation. The group have shown that enantioinduction up to 99% e.e.…”
Section: Scheme 42mentioning
confidence: 99%
“…In this work we focused on the enantioselective reduction of aliphatic ketones into their corresponding alcohols using oxidoreductases, since there is no chemical alternative available that yields similar enantiomeric excess (ee). Long-chain enantiopure aliphatic alcohols are an interesting raw material in the pharmaceutical industry. They have also been used for the production of liquid crystals with interesting optical properties …”
Section: Introductionmentioning
confidence: 99%
“…entry 2) 16. A mixture of Ti(O-iPr)4 /Et 2 Zn resulted in the isolation of the racemic 16 in good yield 17.…”
mentioning
confidence: 99%